La polémica del romanticismo en Manuel de Eduardo de Gorostiza - Reyes Palacios, Felipe (Latin American Theatre Review, 2008)
To appropriately situate the work of Manuel Eduardo de Gorostiza in the history of Mexican and Spanish theatre, it is more important to consider his comedy Las costumbres de antaño (Madrid, 1819; Mexico, 1833) than his more famous work, Contigo pan y cebolla. Different from the latter, which satirizes the vogue for and the conventions of the sentimental novel of pre-romanticism, the former is dedicated to questioning directly the postulates of historical Romanticism of German origin, whose introduction in Spain dates to this time. Gorostiza’s critical stance is reaffirmed, in the theoretical realm, by the four articles that make up “On the Modern Spanish Theatre,” published in London during his exile (1824). These articles have been inexplicably forgotten, and upon their review it becomes evident that the author chose both of these comedias to commemorate his return to Mexico in 1833, as if he satirically presaged the advent of Romanticism in this country, which would soon appear in the dramas of Fernando Calderón and Ignacio Rodríguez Galván. (FRP, Article in Spanish)